2016
DOI: 10.1149/07515.0287ecst
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fluid Dynamics on the Electrochemical Deposition of Tantalum

Abstract: In the electrochemical deposition of Tantalum from ionic liquids at moderate temperatures, the preparation of purely metallic coatings with thicknesses in the micrometer range and the accurate control of the crystallographic parameters remain challenging. In this work, preliminary experiments on the influence of fluid dynamics during the electrodeposition of tantalum in the ionic liquid 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl) imide using ultrasound as an additional source of energy were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As we use a passive measurement method, the method can be applied even in the presence of ultrasound. This had been demonstrated in detail for aqueous solutions (51)(52)(53)(54)(55) and recently also for ILs (45). In related work, we studied the electrochemical reduction of NbCl 5 in BMP TFSI using the EQCM technique.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…As we use a passive measurement method, the method can be applied even in the presence of ultrasound. This had been demonstrated in detail for aqueous solutions (51)(52)(53)(54)(55) and recently also for ILs (45). In related work, we studied the electrochemical reduction of NbCl 5 in BMP TFSI using the EQCM technique.…”
Section: Introductionmentioning
confidence: 89%
“…In the following, also the influence of ultrasound on the deposition of tantalum at room temperature was studied. In earlier work, it had been shown that ultrasound has both a positive effect in voltammetry and during potentiostatic experiments (45). However, those experiments had been carried out without any cooling.…”
Section: Electrodeposition Of Tantalummentioning
confidence: 99%
See 2 more Smart Citations